Chloroplast and Cytoplasmic Enzymes: IV. Pea Leaf Fructose 1,6-Diphosphate Aldolases - Anderson, Louise E. (1972)
Several peaks of aldolase activity are found in the isoelectric focusing pattern of pea (Pisum sativum) leaf chloroplast extracts. One peak, separated by 0.5 pH unit from the major chloroplast aldolase peak, is found when cytoplasmic extracts are focused. The chloroplast and cytoplasmic enzymes have a pH 7.4 optimum with fructose 1,6-diphosphate. The Michaelis constant for fructose-1,6-diphosphate is 19 μM for the chloroplast, 21 μM for the cytoplasmic enzyme, and for sedoheptulose 1,7-diphosphate, 8 μM for the chloroplast enzyme, 18 μM for the cytoplasmic enzyme. Both enzymes are inhibited by d-glyceraldehyde 3-phosphate and by ribulose 1,5-diphosphate. The similarity in the catalytic properties of the isoenzymes suggests that both enzymes have an amphibolic role in carbon metabolism in the green leaf.